EXPLORATION OF VALUE-AT-RISK AND VALUE-AT-RISK MODIFICATION RISK MEASURE - JULAISA SARAGIH ( 10113060 ), CHRISTINE
Value-at-Risk (VaR) is one of popular risk measure used in risk management. This risk measure will use the infimum of risk distribution function and does not consider the magnitude of risk factor. Some improvements of VaR are studied in order to obtain a better risk measure. VaR can be improved by correcting its coverage probability to produce Improved-VaR with desired coverage probability. Other modifications are made by providing a new risk measure as an alternative having coherent properties of a risk measure, ie Expected Shortfall (ES) and risk measure with distortion function. ES will be very useful if losses are over VaR prediction. Meanwhile, the distorted risk measure is obtained by shaping adjusted losses from the existing loss data so that this measure will depend only on the distribution and their distorted functions parameters. The use of right risk measures will be depended by loss data by considering the characteristics of each risk measure